2018
DOI: 10.1002/ijfe.1653
|View full text |Cite
|
Sign up to set email alerts
|

Volatility spillovers between real exchange rate returns and real stock price returns in Malaysia

Abstract: This study analyses volatility spillovers between real exchange rate returns and real stock price returns in Malaysia. The component‐generalized autoregressive conditional heteroskedasticity model with asymmetric effect is used to decompose volatility into permanent or long‐run component and transitory or short‐run component. Permanent and transitory components of volatility are commonly high in the global financial crisis, 2008. The results of the seemingly unrelated regressions framework show that volatility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…However, under different thresholds, the relationship between variables is usually nonlinear (Tian et al 2020). Several recent studies have pointed out that the symmetry assumption may underestimate the impact of exchange rates on stock prices (Effiong and Bassey 2019;Wong 2019;Salisu et al 2020). Ismail and Isa (2009) concluded that a nonlinear model is more appropriate.…”
Section: The Effects Of Exchange Rates On Stock Pricesmentioning
confidence: 99%
“…However, under different thresholds, the relationship between variables is usually nonlinear (Tian et al 2020). Several recent studies have pointed out that the symmetry assumption may underestimate the impact of exchange rates on stock prices (Effiong and Bassey 2019;Wong 2019;Salisu et al 2020). Ismail and Isa (2009) concluded that a nonlinear model is more appropriate.…”
Section: The Effects Of Exchange Rates On Stock Pricesmentioning
confidence: 99%
“…Exchange rate and stock price are said to be closely linked (Wong, 2018). Multinational firms are involved in international transactions, and their profits are strongly influenced by real exchange rates.…”
Section: The Impact Of Real Exchange Ratesmentioning
confidence: 99%
“…Frankel (1983) and Branson (1981) proposed the portfolio balance theory to deliver a much more comprehensive result. Moreover, Wong (2018) found that there is a significant relationship between competitiveness exchange rate and stock market in Malaysia by examining the spillover permanent component volatility and transitory component volatility between real exchange rate return and real stock prices, which in turn leads to stronger permanent component volatility spillover rather than In contrast, Bahmani-Oskooee and Saha (2016) demonstrated a significant positive correlation between exchange rate and the stock market, concentrating on export-oriented firms in Brazil, Canada, Chile, Indonesia, Japan, Korea, Malaysia, and Mexico by applying the NARDL estimates. In addition, recent study by Vadivel (2021) found a negative relationship between exchange rate and stock market price for India and South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%